Hegelian Idealism as the Self-Consciousness of Modernity - Paixão, João Gabriel (Revista Eletrônica Estudos Hegelianos, 2023)
In this article, we intend to demonstrate the symbolic dimension of the meaning of absolute knowledge in Hegel’s philosophy. As the realization of the journey of Spirit into itself, it is also the glory of metaphysics of subjectivity, that is, the glory of subjectivity as the grounding of all knowledge, of all history and of Being itself. In a historical-political sense, it is the self-consciousness of the realization of modernity. To present the philosophy of Hegel, we are going to show how the first shape of consciousness, namely the sense-certainty, works as an opposition to Hegel’s absolute idealism, mainly because it is a-theorical and it gives itself to experience rather than to knowledge. That is why sense-certainty has to be sublated; ultimately this sublation eventually becomes absolute knowledge or self-knowing spirit. This process of sublation occurs as the ultimate realization of metaphysics, as well as of the history of mankind itself. We try to show this process of coming to be of knowledge in his study of history as well as through the passage in the Phenomenology of Spirit of religion to philosophy as absolute knowledge.